SAT0196 Vitamin D Status and Clinical Significance in a Group of Scleroderma Patients. (23rd January 2014) - Groseanu, L.; Saulescu, Ioana; Balanescu, Andra; Bojinca, Violeta; Opris, Daniela; Constantinescu, Cosmin; Berghea, Florian; Abobului, Mihai; Predeteanu, Denisa; Ionescu, Ruxandra
Abstract : Background: Epidemiological evidence indicates a significant association between vitamin D deficiency and an increased incidence of several autoimmune diseases. Low vitamin D levels have also been reported in patients with systemic sclerosis (SSc), but the number of studies is limited with conflicting data. Objectives: To investigate 25-OH vitamin D concentrations in a group of systemic sclerosis (SSc) patients and establish connections between a deficient vitamin D status and SSc disease activity and severity or on the clinical consequences that such deficiency might cause. Methods: 44 scleroderma patients were evaluated during June 2010 - June 2012 in InternalMedicine and Rheumatology Department of Sf. Maria Hospital, Bucharest, Romania. All patients gave informed consent for all procedures, which were carried out with the local ethics committee's approval. We performed a complete evaluation of all patients following: MEDS evaluation sheets; disease activity was evaluated with the Disease Activity Score (DAS) according to the European Scleroderma Study Group guidelines, HAQ (Health assessment questionnaires) have been also completed. Vitamin D was measured with the RIA Diasorin kit or expressed as"RIA Diasorin equivalent". According to current recommendations, vitamin D concentrations < 30 ng/ml were considered as indicating insufficiency, while values < 10 ng/ml were classified as deficiency Results: 95, 45% of all patients were women, 56, 81% had diffuse skin involvement, mean age 35, 9 years, medium disease duration 12, 5 years+/- 3, 4. mean Rodnan 9, 5+/-2, 4, mean activity score=3, 13+/- 0, 8, mean Medsger 6, 66+/- 1, 1. 36, 36% had interstitial lung disease, 18, 7% had pulmonary hypertension. Only 3 patients had optimal levels of 25(OH)2 D; most of the patients had an insufficient (65, 9%) or deficient (27, 27%)level, mean vitamin D serum concentration was/18, 6+/-3, 5ng/ml. A negative correlation between patients' age and vitamin D concentration was observed. A significant correlations were found between low vitamin D levels and age, Rodnan score, European disease activity score, Medsger score, pulmonary fibrosis and low DLCO., distal joint contracture, muscular weakness/myalgia. Conclusions: Most of the patients of the group had suboptimal low levels of vitamnin D. Some clinical correlations were indentified. We are aware of the limitations of the study that are : small group, lack of control group and the fact that measurements of vitamin D were not done in the same period of the year. Given the most recent findings, we consider further research would be clinically important to elucidate the causes of hypovitaminosis D in SSc, its relevance to disease progression, its influence on immune functions, and the potential effects of supplementation References: Rios-Fernández R et al Bone mass and vitamin D in patients with systemic sclerosis from two Spanish regions. Clin Exp Rheumatol. 2012 Nov-Dec;30(6):905-11. Vacca A, Cormier C, Mathieu A, Kahan A, Allanore Y. Vitamin D levels and potentialimpact in systemic sclerosis. Clin Exp Rheumatol. 2011 Nov-Dec;29(6):1024 Arnson Y, Serum 25-OH vitamin D concentrations are linked with various clinical aspects in patients with systemic sclerosis: a retrospective cohort study and review of the literature. Autoimmun Rev. 2011 Jun;10(8):490-4. doi: 10.1016/j.autrev.2011.02.002. Disclosure of Interest: None Declared